Między wojną a pokojem. Procesy urbanizacyjne i ich skutki w południowosudańskim mieście - Maciej Kurcz (Studia Etnologiczne i Antropologiczne, 2010)
Juba, located in the southern Sudan, used to be a small African place, devastated by war and inhabited by a small handful of haggard people. Currently, almost a day by day, it is becoming a big city and the capital of autonomous sothern provinces. For the last 50 years southern Sudan has been the arena of one of the bloodiest and longest con¬flicts in the history of postcolonial Africa. The black and Christian people struggled with the Muslim majority in an unequal battle. Hundreds of peole died or survived escaping to neighbouring African countries. Many inhabitants of the south, deported to the northern provinces, were given to Muslim caretakers, often enslaving them. The war finished at the beginning of our century without any deci¬sion. As a result of the peace treaty from 2005, rebellious provinces were given a big autonomy, and, in the future even the chance of self decision. An important element of the compromise was also a division of benefits from oil sale, exploited from the sources in the southern Sudan. The very richness has become the so called modus vivendi of the Sudanese conflict, making Chartum aware of war unprofitability. This memorable event has become the beginning of substantial and abrupt transformations touching upon almost each aspect of the region (an economic and political situation, as well as social or religious relations). The authors of the project Juba, the centre of cultures and conflicts, try to describe and understand the changes taking place. They assume a series of ethnographic terrain works in this very place aiming at the presentation of the real life of small town inhabitants in the widest way, as well as give data on the functioning of the so called traumatic society — the phenomenon extremely important for many countries of the contemporary Africa suffering from war not such a long ago which achieved stabilization. The material derives from the first survey excursion to Juba realized between February and March 2007.